Magnetic sulfonated covalent organic polymer adsorbent, preparation method and application thereof, and phenylurea detection method
By using magnetic sulfonated covalent organic polymer adsorbent, the problem of insufficient adsorption properties of existing adsorbents by phenylurea is solved, and efficient adsorption effect and good reusability are achieved.
Patent Information
- Application Number
- CN202411745285.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-03-18
AI Technical Summary
The existing porous organic polymer adsorbents have poor selective adsorption properties for phenylurea pesticides in food, resulting in low adsorption rate, which in turn produces large errors in determining the residual level of BUs in food.
A magnetic sulfonated covalent organic polymer adsorbent is used, which consists of a covalent organic frame and Fe3O4@SiO2 magnetic nanoparticles loaded on the covalent organic frame. The adsorption performance is improved by introducing sodium sulfonate groups and magnetic nanoparticles are made to be magnetic by loading magnetic nanoparticles.
The adsorption rate of p-phenyleurea is significantly improved to reach more than 92%, reducing the error in determining the BUs residue level in food, and the adsorbent has good magnetic, hydrophilicity and thermal stability, which is suitable for reuse.
Smart Images

Figure CN119633771A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of adsorbents, and in particular to a magnetic sulfonated covalent organic polymer adsorbent, a preparation method and application thereof, and a phenylurea detection method. Background Art
[0002] Phenylurea insecticides (BUs) include diflubenzuron (DFZ), flufenoxuron (TFM), hexaflumuron (HFM), flubendiamide (TFZ), flufenoxuron (FFX) and chlorpyrifos (CFZ). They have the characteristics of high insecticidal activity, low environmental persistence and low toxicity, and have been widely used in agricultural production. However, the widespread use of phenylurea insecticides will lead to residual pollution in the environment and harm to human health. The national food safety standard sets the maximum residue level of BUs at 0.5-1.0 mg kg -1 , exceeding the above values will cause harm to human health. Therefore, it is very important to accurately determine the residual level of BUs in food for controlling food safety.
[0003] At present, commonly used sample pretreatment technologies include solid phase extraction and magnetic solid phase extraction, among which magnetic solid phase extraction (MSPE) has many advantages such as simple operation, fast processing speed, and small amount of solvent required. In this process, adsorbents are the core that determines the extraction efficiency.
[0004] As adsorbents for sample pretreatment, porous organic polymers have attracted much attention in the field of adsorption of organic pollutants due to their many advantages, such as large specific surface area, controllable synthesis, and diverse functionalization. Compared with other porous organic materials, they have the advantages of simple synthesis methods, adjustable pore size, and easy functionalization. However, the porous organic polymers currently available on the market have poor selective adsorption for BUs in food, resulting in a low adsorption rate, generally around 35-80%. This leads to large errors in the determination of the residual level of BUs in food, making the residual level of BUs in the food far lower than the actual level, resulting in some unqualified foods being sold on the market, causing great harm to the health of consumers.
[0005] Therefore, how to improve the selective adsorption of organic polymer adsorbents for BUs has become a technical problem that needs to be solved urgently in this field. Summary of the invention
[0006] The purpose of the present invention is to provide a magnetic sulfonated covalent organic polymer adsorbent, a preparation method and application thereof, and a detection method for phenylurea. The magnetic sulfonated covalent organic polymer adsorbent provided by the present invention has high selective adsorption for BUs, so that the adsorption rate of the magnetic sulfonated covalent organic polymer adsorbent for BUs reaches more than 92%.
[0007] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0008] The invention provides a magnetic sulfonated covalent organic polymer adsorbent, comprising a covalent organic framework and Fe3O4@SiO2 magnetic nanoparticles loaded on the covalent organic framework; the building units of the covalent organic framework are trialdehyde phloroglucinol and sodium 2,5-diaminobenzenesulfonate.
[0009] Preferably, the molar ratio of trialdehyde phloroglucinol to sodium 2,5-diaminobenzenesulfonate in the covalent organic framework is 6:(8-10).
[0010] Preferably, the ratio of the amount of trialdehyde phloroglucinol in the covalent organic framework to the mass of Fe3O4@SiO2 magnetic nanoparticles is 6 mmol: (280-300) mg.
[0011] Preferably, the Fe3O4@SiO2 magnetic nanoparticles include Fe3O4 nanoparticles and SiO2 coated on the surface of the Fe3O4 nanoparticles.
[0012] The present invention provides a method for preparing the magnetic sulfonated covalent organic polymer adsorbent described in the above technical solution, comprising the following steps:
[0013] (1) mixing trialdehyde phloroglucinol, 2,5-diaminobenzenesulfonic acid and an organic solvent to obtain a mixed solution;
[0014] (2) The mixed solution obtained in step (1) is mixed with Fe3O4@SiO2 magnetic nanoparticles and sodium acetate solution and then subjected to a solvothermal reaction to obtain a magnetic sulfonated covalent organic polymer adsorbent.
[0015] Preferably, in step (1), the ratio of the amount of trialdehyde phloroglucinol to the volume of the organic solvent is 0.6 mmol: (8-15) mL.
[0016] Preferably, the molar ratio of trialdehyde phloroglucinol in the mixed solution of step (2) to sodium acetate in the sodium acetate solution is 6:(0.05-0.2).
[0017] Preferably, the temperature of the solvent thermal reaction in step (2) is 100 to 150° C., and the time of the solvent thermal reaction is 48 to 108 hours.
[0018] The present invention provides the use of the magnetic sulfonated covalent organic polymer adsorbent described in the above technical solution or the magnetic sulfonated covalent organic polymer adsorbent prepared by the preparation method described in the above technical solution in adsorbing phenylurea.
[0019] The present invention provides a method for detecting phenylurea, comprising the following steps:
[0020] 1) Mixing the sample solution to be tested and the adsorbent for extraction and adsorption, and then performing magnetic separation to obtain a saturated adsorbent; the adsorbent is the magnetic sulfonated covalent organic polymer adsorbent described in the above technical solution or the magnetic sulfonated covalent organic polymer adsorbent prepared by the preparation method described in the above technical solution; the salinity of the sample solution to be tested is ≤9%, and the pH value of the sample solution to be tested is 3-7; the volume ratio of the sample solution to be tested and the mass ratio of the magnetic sulfonated covalent organic polymer adsorbent is 50mL: (25-30)mg; the extraction and adsorption time is 5-20min;
[0021] 2) eluting the saturated adsorbent obtained in step 1) and filtering to obtain an eluent and an eluted adsorbent; the eluent used for the elution is methanol, acetone or acetonitrile; the ratio of the mass of the magnetic sulfonated covalent organic polymer adsorbent to the volume of the eluent is 25 mg: (0.3-0.9) mL;
[0022] 3) performing high performance liquid chromatography-ultraviolet detection on the phenylurea in the eluent obtained in step 2) to obtain the adsorption amount of the adsorbent on the phenylurea.
[0023] The invention provides a magnetic sulfonated covalent organic polymer adsorbent, comprising a covalent organic framework and Fe3O4@SiO2 magnetic nanoparticles loaded on the covalent organic framework; the building units of the covalent organic framework are trialdehyde phloroglucinol and sodium 2,5-diaminobenzenesulfonate. The magnetic sulfonated covalent organic polymer provided by the present invention uses trialdehyde pyrogallol and sodium 2,5-diaminobenzenesulfonate as building units of covalent organic frameworks (COFs), utilizes the porous structure of COFs, thereby increasing its specific surface area, making it have better adsorption performance, and facilitating the adsorption of Fe3O4@SiO2 magnetic nanoparticles on the surface of the material; at the same time, by introducing sodium sulfonate groups, the selective adsorption of BUs by the organic polymer adsorbent is greatly improved, thereby improving the adsorption performance of the adsorbent for BUs; by loading Fe3O4@SiO2 magnetic nanoparticles on COFs, the organic polymer adsorbent can be made magnetic, on the one hand, the magnetism of the magnetic nanoparticles has better adsorption capacity for small molecules, which can further improve the adsorption performance of the adsorbent for BUs, and on the other hand, it is conducive to its separation from the sample solution during the detection process of the sample solution, thereby facilitating reuse and reducing costs. The results of the embodiments show that the adsorption rate of BUs by the magnetic sulfonated covalent organic polymer adsorbent (M-TpPa-SO3Na) provided by the present invention reaches 92.5% to 98.7%, while the adsorption rate of M-TpPa-SO3H is only 78.6% to 79.4%, and the adsorption rate of M-TpPa is only 35.1% to 40.8%; at the same time, the magnetic sulfonated covalent organic polymer adsorbent has good magnetism, hydrophilicity and thermal stability. The used magnetic sulfonated covalent organic polymer adsorbent can be reused after cleaning with acetonitrile and distilled water, and has good cyclic stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is the element distribution diagram of M-TpPa-SO3Na obtained in Example 1 of the present invention;
[0025] Figure 2 This is a transmission electron microscopy image of M-TpPa-SO3Na obtained in Example 1 of the present invention;
[0026] Figure 3 FT-IR spectrum of M-TpPa-SO3Na obtained in Example 1 of the present invention;
[0027] Figure 4 This is the VSM diagram of M-TpPa-SO3Na obtained in Example 1 of the present invention;
[0028] Figure 5 This is a hydrophilicity test diagram of M-TpPa-SO3Na obtained in Example 1 of the present invention;
[0029] Figure 6 This is the XPS graph of M-TpPa-SO3Na obtained in Example 1 of the present invention;
[0030] Figure 7 Thermogravimetric curves of the magnetic sulfonated covalent organic polymer adsorbents obtained in Example 1 and Comparative Examples 1-2;
[0031] Figure 8 The X-ray diffraction patterns of the magnetic sulfonated covalent organic polymer adsorbents obtained in Example 1 and Comparative Example 2;
[0032] Fig. 9 The curves showing the effect of the amount of adsorbent on the BUs adsorption recovery rate in Application Examples 1 to 2 and Comparative Application Examples 1 to 3;
[0033] Fig.10 The curves showing the effect of extraction adsorption time on BUs adsorption recovery rate in application examples 1, 3 to 5 and comparative application example 4;
[0034] Fig.11 The curves are the influence of the concentration of sodium chloride on the BUs adsorption recovery rate in Application Example 1, Application Examples 6-8 and Comparative Application Examples 5-6;
[0035] Fig.12 The curves are the influence of the pH value of the sample solution on the BUs adsorption recovery rate in Application Example 1, Application Examples 9-11 and Comparative Application Examples 7-8;
[0036] Fig.13 The acid-base stability test curve of M-TpPa-SO3Na provided in Example 1;
[0037] Fig.14 The curves showing the effect of the type of eluent on the BUs adsorption recovery rate in Application Examples 1 and Application Examples 12-13;
[0038] Fig.15 The curves showing the effect of the amount of the eluent used on the BUs adsorption recovery rate in Application Examples 1 and Application Examples 14 to 17;
[0039] Fig.16 This is the effect of the volume of the eluent on the detection sensitivity of the adsorbent in Application Example 1 and Application Examples 14 to 17. DETAILED DESCRIPTION
[0040] The invention provides a magnetic sulfonated covalent organic polymer adsorbent, comprising a covalent organic framework and Fe3O4@SiO2 magnetic nanoparticles loaded on the covalent organic framework; the building units of the covalent organic framework are trialdehyde phloroglucinol and sodium 2,5-diaminobenzenesulfonate.
[0041] The magnetic sulfonated covalent organic polymer adsorbent provided by the present invention comprises a covalent organic framework, the building blocks of which are trialdehyde phloroglucinol and sodium 2,5-diaminobenzenesulfonate. In the present invention, the molar ratio of trialdehyde phloroglucinol and sodium 2,5-diaminobenzenesulfonate in the covalent organic framework is preferably 6: (8-10), more preferably 6: 9.
[0042] The magnetic sulfonated covalent organic polymer adsorbent provided by the present invention also includes Fe3O4@SiO2 magnetic nanoparticles loaded on the covalent organic framework. In the present invention, the mass ratio of the amount of trialdehyde phloroglucinol in the covalent organic framework to the mass of Fe3O4@SiO2 magnetic nanoparticles is preferably 6mmol:(280-300)mg, more preferably 6mmol:(285-295)mg, and further preferably 6mmol:(290-295)mg. The present invention further improves the selective adsorption of the magnetic sulfonated covalent organic polymer adsorbent for BUs by controlling the ratio of each component.
[0043] In the present invention, the Fe3O4@SiO2 magnetic nanoparticles preferably include Fe3O4 nanoparticles and SiO2 coated on the surface of the Fe3O4 nanoparticles. In the present invention, the Fe3O4@SiO2 magnetic nanoparticles are preferably spherical particles. The present invention has no particular limitation on the specific size of the Fe3O4@SiO2 magnetic nanoparticles, and the Fe3O4@SiO2 magnetic nanoparticles can be prepared by methods well known to those skilled in the art.
[0044] The magnetic sulfonated covalent organic polymer provided by the present invention uses trialdehyde pyrogallol and sodium 2,5-diaminobenzenesulfonate as building units of covalent organic frameworks (COFs), utilizes the porous structure of COFs, thereby increasing its specific surface area, making it have better adsorption performance, and facilitating the adsorption of Fe3O4@SiO2 magnetic nanoparticles on the surface of the material; at the same time, by introducing sodium sulfonate, the selective adsorption of BUs by the organic polymer adsorbent is greatly improved, thereby improving the adsorption performance of the adsorbent for BUs; by loading Fe3O4@SiO2 magnetic nanoparticles on COFs, the organic polymer adsorbent can be made magnetic, and on the one hand, the magnetism of the magnetic nanoparticles has better adsorption capacity for small molecules, which can further improve the adsorption performance of the adsorbent for BUs, and on the other hand, it is conducive to its separation from the sample solution during the detection process of the sample solution, thereby facilitating reuse and reducing costs.
[0045] The present invention also provides a method for preparing the magnetic sulfonated covalent organic polymer adsorbent described in the above technical solution, comprising the following steps:
[0046] (1) mixing trialdehyde phloroglucinol, 2,5-diaminobenzenesulfonic acid and an organic solvent to obtain a mixed solution;
[0047] (2) The mixed solution obtained in step (1) is mixed with Fe3O4@SiO2 magnetic nanoparticles and sodium acetate solution and then subjected to a solvothermal reaction to obtain a magnetic sulfonated covalent organic polymer adsorbent.
[0048] In the present invention, unless otherwise specified, the raw materials used are commercially available products well known to those skilled in the art.
[0049] The invention mixes trialdehyde phloroglucinol, 2,5-diaminobenzenesulfonic acid and an organic solvent to obtain a mixed solution.
[0050] In the present invention, the molar ratio of the trialdehyde phloroglucinol to 2,5-diaminobenzenesulfonic acid (Pa-SO3H) is preferably 6: (8-10), more preferably 6: 9. The present invention can improve the conversion rate of raw materials, avoid the waste of raw materials, and reduce production costs by controlling the usage relationship of trialdehyde phloroglucinol and 2,5-diaminobenzenesulfonic acid.
[0051] In the present invention, the ratio of the amount of trialdehyde phloroglucinol to the volume of the organic solvent is preferably 0.6 mmol: (8-15) mL. The present invention can ensure that the raw materials are completely dissolved in the solvent and react by controlling the amount relationship of each component.
[0052] In an embodiment of the present invention, the ratio of the amount of trialdehyde pyrogallol to the volume of the organic solvent is 0.6mmol:8mL, 0.6mmol:9mL, 0.6mmol:10mL, 0.6mmol:11mL, 0.6mmol:12mL, 0.6mmol:13mL, 0.6mmol:14mL or 0.6mmol:15mL.
[0053] In the present invention, the preparation method of the trialdehyde phloroglucinol (TP) is preferably as follows: phloroglucinol and hexamethylenetetramine are first mixed, trifluoroacetic acid is then added dropwise, stirred for 3 h at a temperature of 90 to 100 ° C in a N2 atmosphere, and then 3 mol L -1 The hydrochloric acid is subjected to Duff reaction, cooled to room temperature to obtain a mixture, and finally the mixture is filtered through diatomaceous earth, extracted with dichloromethane, dehydrated with anhydrous magnesium sulfate, filtered with filter paper and rotary evaporated in sequence to obtain trialdehyde phloroglucinol. In an embodiment of the present invention, the molar ratio of the phloroglucinol to hexamethylenetetramine is 23.8:53.9; the volume ratio of the molar ratio of the phloroglucinol to trifluoroacetic acid is 23.8mmol:45mL; the volume ratio of trifluoroacetic acid to hydrochloric acid is 45:70; the temperature of the Duff reaction is 90-100°C; and the time of the Duff reaction is 1h. The trialdehyde phloroglucinol obtained by the present invention is a yellow solid.
[0054] In the present invention, the organic solvent preferably includes 1,4-dioxane and mesitylene; the volume ratio of the 1,4-dioxane and mesitylene is preferably 1:(2-5). In the present invention, the 1,4-dioxane and mesitylene as solvents can provide reaction conditions.
[0055] In an embodiment of the present invention, the volume ratio of 1,4-dioxane to mesitylene is 1:2, 1:3, 1:4 or 1:5.
[0056] As an embodiment of the present invention, the operation of mixing the trialdehyde phloroglucinol, 2,5-diaminobenzenesulfonic acid and the organic solvent can be: firstly mix the trialdehyde phloroglucinol and 2,5-diaminobenzenesulfonic acid, then add the organic solvent, and finally perform ultrasonic treatment to obtain a mixed solution. As an embodiment of the present invention, the ultrasonic treatment time can be 5 to 15 minutes, or 10 minutes. The present invention does not have any special limitation on the ultrasonic power during the ultrasonic treatment, which can be determined according to the technical common sense of those skilled in the art, so long as the raw materials can be mixed evenly. The present invention can improve the uniformity of raw material mixing by mixing in the above manner.
[0057] After obtaining the mixed solution, the present invention mixes the mixed solution with Fe3O4@SiO2 magnetic nanoparticles and sodium acetate solution and then performs a solvent thermal reaction to obtain a magnetic sulfonated covalent organic polymer adsorbent.
[0058] In the present invention, the mass ratio of the amount of trialdehyde pyrogallol to the mass of Fe3O4@SiO2 magnetic nanoparticles in the mixed solution is preferably 6mmol:(280-300)mg, more preferably 6mmol:(285-295)mg, and further preferably 6mmol:(290-295)mg.
[0059] In the present invention, the concentration of the sodium acetate solution is preferably 3 to 6 mol L -1 ; The solvent in the sodium acetate solution is preferably water; the molar ratio of trialdehyde phloroglucinol in the mixed solution to sodium acetate in the sodium acetate solution is preferably 6:(0.05-0.2), more preferably 6:(0.1-0.15). The present invention can introduce sodium ions by adding sodium acetate solution, on the one hand, to form sodium 2,5-diaminobenzenesulfonate with 2,5-diaminobenzenesulfonic acid, and on the other hand, sodium acetate can improve the efficiency of the solvent thermal reaction, and when sodium ions and 2,5-diaminobenzenesulfonic acid form sodium 2,5-diaminobenzenesulfonate, sodium acetate will be converted into acetic acid, and acetic acid can still be used as a catalyst to accelerate the reaction.
[0060] As an embodiment of the present invention, the concentration of the sodium acetate solution can be 3 mol L -1 , 4 mol L -1 , 5 mol L -1 or 6 mol L -1 .
[0061] In the present invention, the preparation method of the Fe3O4@SiO2 magnetic nanoparticles is preferably as follows: firstly, FeCl3·6H2O, sodium acetate and ethylene glycol are ultrasonically mixed and then subjected to a first hydrolysis reaction, then filtered, washed with ethanol and water to obtain Fe3O4 nanoparticles, then the Fe3O4 nanoparticles, deionized water and ethanol are ultrasonically mixed for 5 to 10 minutes, concentrated ammonia water and tetraethyl orthosilicate are slowly added to the homogeneous solution, and then a second hydrolysis reaction is carried out, and finally, magnetic separation, ethanol and water washing and drying are carried out in sequence to obtain Fe3O4@SiO2 magnetic nanoparticles. In an embodiment of the present invention, the mass of the FeCl3·6H2O, the mass of the sodium acetate and the volume of the ethylene glycol are in a ratio of 0.65g:2.6g:60mL; the temperature of the first hydrolysis reaction is 200 to 220°C; the time of the first hydrolysis reaction is 6 to 7h; the first hydrolysis reaction is carried out in a reactor; and the cooling method of the first hydrolysis reaction is natural cooling. In an embodiment of the present invention, the ratio of the mass of the Fe3O4 nanoparticles, the volume of water and the volume of ethanol is 1.4g:70mL:280mL; the concentration of the concentrated ammonia water is 30wt%; the ratio of the mass of the Fe3O4 nanoparticles, the volume of the concentrated ammonia water and the volume of tetraethyl orthosilicate (TEOS) is 1.4g:2mL:1mL; the time of the second hydrolysis reaction is 8h; the temperature of the second hydrolysis reaction is room temperature; the second hydrolysis reaction is carried out under mechanical stirring. As an embodiment of the present invention, the drying temperature is 60-70℃; the drying time is 24h; the drying is carried out in a vacuum drying oven.
[0062] In the present invention, the temperature of the solvent thermal reaction is preferably 100 to 180°C; the time of the solvent thermal reaction is preferably 48 to 108 hours; and the solvent thermal reaction is preferably carried out in an autoclave. The present invention does not specifically limit the specific model and source of the autoclave, and a commercially available autoclave familiar to those skilled in the art can be used. The present invention uses a solvent thermal reaction to polymerize TP and Pa-SO3H into an organic polymer, while Pa-SO3H reacts with sodium acetate to generate Pa-SO3Na, and in this process, Fe3O4@SiO2 magnetic nanoparticles can adhere to the surface of the organic polymer; by controlling the parameters of the solvent thermal reaction, the specific surface area of the adsorbent can be further increased, thereby improving the adsorption performance of the adsorbent.
[0063] In an embodiment of the present invention, the temperature of the solvent thermal reaction is 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C or 180°C; the time of the solvent thermal reaction is 48h, 60h, 72h, 84h, 96h or 108h.
[0064] After the solvothermal reaction is completed, the present invention preferably sequentially performs magnetic separation, washing and Soxhlet extraction on the product of the solvothermal reaction to obtain a magnetic sulfonated covalent organic polymer adsorbent. The present invention can remove impurities in the product by adopting the above process to obtain a high-purity magnetic sulfonated covalent organic polymer adsorbent.
[0065] In the present invention, the magnetic separation is preferably carried out by using a magnet. The present invention has no particular limitation on the specific operation of the magnetic separation, and the operation well known to those skilled in the art can be used. The present invention can adsorb the adsorbent from the solution by magnetic separation.
[0066] In the present invention, the washing is preferably firstly washed with methanol and then washed with water. The present invention has no particular limitation on the number of washings, which can be determined according to the technical common sense of those skilled in the art as long as the impurities can be removed.
[0067] In the present invention, the Soxhlet extraction is preferably methanol Soxhlet extraction. The present invention has no particular limitation on the specific operation of the Soxhlet extraction, and the operation well known to those skilled in the art can be adopted. The present invention can further remove impurities and improve the purity of the product through Soxhlet extraction.
[0068] The present invention prepares the adsorption material by solvent thermal reaction, so that the obtained adsorbent has a porous structure, improves its specific surface area and adsorption performance, and is conducive to the adsorption of Fe3O4@SiO2 magnetic nanoparticles on the surface of the material, thereby further improving the adsorption capacity of the adsorbent for BUs.
[0069] The present invention also provides the use of the magnetic sulfonated covalent organic polymer adsorbent described in the above technical solution or the magnetic sulfonated covalent organic polymer adsorbent prepared by the preparation method described in the above technical solution in adsorbing phenylurea.
[0070] The present invention has no particular limitation on the specific manner of the application, and any application manner familiar to those skilled in the art may be used.
[0071] The present invention also provides a method for detecting phenylurea, comprising the following steps:
[0072] 1) Mixing the sample solution to be tested and the adsorbent for extraction and adsorption, and then performing magnetic separation to obtain a saturated adsorbent; the adsorbent is the magnetic sulfonated covalent organic polymer adsorbent described in the above technical solution or the magnetic sulfonated covalent organic polymer adsorbent prepared by the preparation method described in the above technical solution;
[0073] 2) eluting the saturated adsorbent obtained in step 1) and filtering to obtain an eluate and an eluted adsorbent;
[0074] 3) performing high performance liquid chromatography-ultraviolet detection on the phenylurea in the eluent obtained in step 2) to obtain the adsorption amount of the adsorbent on the phenylurea.
[0075] The present invention mixes the sample solution to be tested and the adsorbent to perform extraction and adsorption, and then performs magnetic separation to obtain a saturated adsorbent.
[0076] The present invention has no special limitation on the type of the sample to be tested, and all substances containing phenylurea can be used as the sample to be tested. As an embodiment of the present invention, the sample to be tested can be a liquid or a solid; the liquid can be environmental water, honey, or pear juice.
[0077] In the present invention, when the sample to be tested is environmental water, it is preferred to directly use the environmental water as the sample to be tested.
[0078] In the present invention, when the sample to be tested is honey or pear juice, the method for preparing the sample solution to be tested is preferably to mix the sample to be tested with water or methanol to obtain the sample solution to be tested.
[0079] In the present invention, when the sample to be tested is solid, the method for preparing the sample solution to be tested is preferably to crush the sample to be tested, mix it with water or methanol, soak it fully, and then filter it to obtain the sample solution.
[0080] In the present invention, the concentration of BUs in the sample solution to be tested is preferably 50 to 300 ng·g -1 ; The salinity of the sample solution to be tested is ≤9%, preferably 0-3%, and more preferably 0; the pH value of the sample solution to be tested is 3-7, preferably 7.
[0081] The present invention preferably takes 2 to 5 portions of the sample solution of equal volume and mixes them with the adsorbent for extraction and adsorption, and performs multiple groups of tests at the same time. If there are results with extremely large errors, it means that an error occurred during the test and needs to be deleted, thereby reducing the error caused by human operation and improving the accuracy of detection.
[0082] As an embodiment of the present invention, the sample solution to be tested is preferably divided into three portions of equal volume.
[0083] In the present invention, the volume ratio of the sample solution to be tested to the mass ratio of the magnetic sulfonated covalent organic polymer adsorbent is 50 mL: (25-30) mg. The present invention can further improve the adsorption efficiency by controlling the dosage relationship between the two.
[0084] In the present invention, the extraction and adsorption is preferably carried out under oscillation conditions; the extraction and adsorption time is 5 to 20 minutes, preferably 5 to 10 minutes. The present invention has no special limitation on the frequency of the oscillation, and it can be adjusted according to the common sense of those skilled in the art. The present invention can ensure that the adsorbent is in full contact with the BUs in the sample solution to be tested by controlling the extraction and adsorption mode and time, thereby further improving the efficiency of adsorption and improving the adsorption recovery rate.
[0085] The present invention has no special limitation on the specific operation of the magnetic separation, and the separation can be performed using an external magnet.
[0086] After obtaining the saturated adsorbent, the present invention elutes the saturated adsorbent and then filters it to obtain an eluate and an eluted adsorbent.
[0087] Before elution, the present invention preferably removes the residual sample solution in the magnetic sulfonated covalent organic polymer adsorbent after adsorption. The present invention has no special limitation on the specific operation of removing the residual sample solution, and a micro-syringe commonly used by those skilled in the art can be used. Through the above operation, the present invention can reduce the error caused by the residual sample solution to be tested and further improve the adsorption recovery rate.
[0088] In the present invention, the eluent used for elution is methanol, acetone or acetonitrile, preferably acetonitrile; the ratio of the mass of the magnetic sulfonated covalent organic polymer adsorbent to the volume of the eluent is 25 mg: (0.3-0.9) mL, preferably 25 mg: (0.3-0.6) mL; the elution method is preferably vortex elution; the elution time is preferably 1-2 min.
[0089] In the present invention, the filtration preferably uses a 0.22 μm nylon 66 organic membrane.
[0090] In the present invention, the elution adsorbent is preferably washed with acetonitrile and distilled water in sequence. The present invention has no special limitation on the specific amount of acetonitrile and distilled water used in the washing, and it is determined according to the technical common sense of those skilled in the art, as long as the impurities in the magnetic sulfonated covalent organic polymer adsorbent can be removed. The present invention can remove impurities in the magnetic sulfonated covalent organic polymer adsorbent by washing it, and then reuse it, which greatly reduces the cost of detection.
[0091] After obtaining the eluent, the present invention performs high performance liquid chromatography-ultraviolet detection on the phenylurea in the eluent to obtain the adsorption amount of the adsorbent on the phenylurea.
[0092] In the present invention, the equipment and parameters used for the high performance liquid chromatography-ultraviolet detection are preferably: chromatographic system: 1260-HPLC (Agilent, USA), UV detector and binary pump system; chromatographic column: C18 chromatographic column (250mm×4.6mm, 5.0μm); mobile phase: acetonitrile and water; the volume ratio of acetonitrile and water is 73:27, and the flow rate is 1.0mLmin -1 ; Detection wavelength: 254nm, injection volume: 20μL.
[0093] The present invention preferably removes data that are obviously different from other data in the obtained results, and then takes the average value. The present invention can reduce the impact of other factors on the accuracy by removing parameters with obvious problems, and then taking the average value, which can improve the accuracy of the detection.
[0094] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0095] Example 1
[0096] A magnetic sulfonated covalent organic polymer adsorbent, comprising a covalent organic framework and Fe3O4@SiO2 magnetic nanoparticles loaded on the covalent organic framework; the building units of the covalent organic framework are trialdehyde phloroglucinol and sodium 2,5-diaminobenzenesulfonate; the molar ratio of trialdehyde phloroglucinol and sodium 2,5-diaminobenzenesulfonate in the covalent organic framework is 6:9; the mass ratio of trialdehyde phloroglucinol in the covalent organic framework to Fe3O4@SiO2 magnetic nanoparticles is 6mmol:295mg; the Fe3O4@SiO2 magnetic nanoparticles are composed of Fe3O4 nanoparticles and SiO2 coated on the surface of the Fe3O4 nanoparticles;
[0097] The preparation method is as follows:
[0098] (1) firstly, trialdehyde phloroglucinol (Tp) and 2,5-diaminobenzenesulfonic acid (Pa-SO3H) are mixed, then an organic solvent is added, and finally an ultrasonic treatment is performed for 10 minutes to obtain a mixed solution; the molar ratio of the trialdehyde phloroglucinol and 2,5-diaminobenzenesulfonic acid is 6:9; the organic solvent is a mixture of 1,4-dioxane and mesitylene, and the volume ratio of 1,4-dioxane and mesitylene is 1:4; the molar ratio of the trialdehyde phloroglucinol and the volume of the organic solvent is 0.6 mmol:10 mL;
[0099] (2) Adding Fe3O4@SiO2 magnetic nanoparticles and sodium acetate solution to the mixed solution obtained in step (1), then performing a solvent thermal reaction in an autoclave, and finally performing magnetic separation, washing and methanol Soxhlet extraction in sequence to obtain a magnetic sulfonated covalent organic polymer adsorbent, recorded as M-TpPa-SO3Na; the mass ratio of the trialdehyde phloroglucinol to the mass of the Fe3O4@SiO2 magnetic nanoparticles is 6 mmol:295 mg, and the concentration of the sodium acetate solution is 5 mol L -1 The molar ratio of trialdehyde phloroglucinol in the mixed solution to sodium acetate in the sodium acetate solution is 6:0.1, and the solvent in the sodium acetate solution is water; the temperature of the solvent thermal reaction is 120°C, and the time of the solvent thermal reaction is 72h; the magnetic separation is performed by using a magnet, and the washing is first washed with methanol and then washed with water;
[0100] The preparation method of trialdehyde phloroglucinol in step (1) is as follows: phloroglucinol and hexamethylenetetramine are first mixed, trifluoroacetic acid is then added dropwise, and the mixture is stirred at 90° C. in a N2 atmosphere for 3 h, and then 3 mol L of phloroglucinol is added through a dropping funnel. -1 hydrochloric acid for Duff reaction, cooling to room temperature to obtain a mixture, and finally filtering the mixture with diatomaceous earth, extracting with dichloromethane, dehydrating with anhydrous magnesium sulfate, filtering with filter paper and rotary evaporating in sequence to obtain yellow solid trialdehyde phloroglucinol; the molar ratio of phloroglucinol to hexamethylenetetramine is 23.8:53.9; the molar ratio of phloroglucinol to trifluoroacetic acid is 23.8mmol:45mL; the volume ratio of trifluoroacetic acid to hydrochloric acid is 45:70; the temperature of the Duff reaction is 90°C; the time of the Duff reaction is 1h;
[0101] The preparation method of Fe3O4@SiO2 magnetic nanoparticles in step (2) is as follows: firstly, FeCl3·6H2O, sodium acetate and ethylene glycol are ultrasonically mixed and then subjected to a first hydrolysis reaction in a reactor, followed by filtration, ethanol and water washing to obtain Fe3O4 nanoparticles, then the Fe3O4 nanoparticles, deionized water and ethanol are ultrasonically mixed for 5 minutes, concentrated ammonia water and tetraethyl orthosilicate are slowly added to the homogeneous solution, and then a second hydrolysis reaction is carried out under mechanical stirring conditions, and finally, magnetic separation, ethanol and water washing and drying are carried out in sequence to obtain Fe3O4@SiO2 magnetic nanoparticles; the ratio of the mass of FeCl3·6H2O, the mass of sodium acetate and the volume of ethylene glycol is: The ratio of the mass of the Fe3O4 nanoparticles, the volume of water and the volume of ethanol is 1.4g:70mL:280mL; the concentration of the concentrated ammonia water is 30wt%; the ratio of the mass of the Fe3O4 nanoparticles, the volume of the concentrated ammonia water and the volume of tetraethyl orthosilicate (TEOS) is 1.4g:2mL:1mL; the time of the second hydrolysis reaction is 8h, and the temperature of the second hydrolysis reaction is room temperature; the temperature of the drying is 60-70℃, the drying time is 24h, and the drying is carried out in a vacuum drying oven.
[0102] The elemental composition of M-TpPa-SO3Na in Example 1 was observed using an energy dispersive spectrometer. The results are as follows: Figure 1 shown. Figure 1 In the figure, from left to right and from top to bottom, they are Fe, Si, C, N, O, Na and S. The presence and distribution of the above elements indicate the successful preparation of M-TpPaSO3Na.
[0103] The M-TpPa-SO3Na obtained in Example 1 was observed using a transmission electron microscope. Figure 2 As shown. Figure 2 It can be seen that the M-TpPa-SO3Na material has a fibrous structure with spherical Fe3O4@SiO2 magnetic nanoparticles distributed on its surface.
[0104] The M-TpPa-SO3Na obtained in Example 1 was observed using a Fourier transform infrared spectrometer, and the obtained FT-IR spectrum is as follows: Figure 3 As shown. Figure 3 It can be seen that Tp is at 1640cm -1 The C=O stretching vibration disappears at 3417 and 3328 cm -1 The NH stretching vibration disappears at 1586 cm-1 C = C and 1231cm -1 A new characteristic peak appears at CN, indicating that a condensation reaction has occurred.
[0105] The magnetic properties of M-TpPa-SO3Na obtained in Example 1 were characterized by a hysteresis loop measuring instrument (VSM), and the results obtained are as follows: Figure 4 As shown. Figure 4 It can be seen that the curve passes through the origin, is symmetrical and has no hysteresis phenomenon, indicating that M-TpPa-SO3Na has superparamagnetism, and the saturation magnetization value is 22.23emu g -1 , indicating that the adsorption material meets the magnetic requirements.
[0106] The hydrophilicity of the M-TpPa-SO3Na obtained in Example 1 was tested by testing the water contact angle on the surface of the material. The results are as follows: Figure 5 As shown. Figure 5 It can be seen that the water contact angle of M-TpPa-SO3Na is about 17.8°, indicating that M-TpPa-SO3Na is hydrophilic.
[0107] The M-TpPa-SO3Na obtained in Example 1 was subjected to X-ray photoelectron spectroscopy detection, and the obtained XPS graph is as follows: Figure 6 As shown. Figure 6 It can be seen that the absorption peaks of Na1s, O1s, N1s, C1s and S2p appear at 1071.35, 530.91, 398.75, 283.89 and 167.52 eV, respectively, and the absorption peaks of Fe2p and Si2p appear at 710.97 eV and 102.32 eV, respectively.
[0108] Comparative Example 1
[0109] A method for preparing a magnetic covalent organic polymer adsorbent:
[0110] (1) firstly, trialdehyde phloroglucinol and p-phenylenediamine (Pa) are mixed, then a solvent is added, and finally an ultrasonic treatment is performed for 10 minutes to obtain a mixed solution; the molar ratio of the trialdehyde phloroglucinol and p-phenylenediamine is 6:9; the solvent is a mixture of 1,4-dioxane and mesitylene, and the volume ratio of 1,4-dioxane and mesitylene is 1:4; the molar ratio of the trialdehyde phloroglucinol and the volume ratio of the solvent is 0.6 mmol:10 mL;
[0111] (2) Fe3O4@SiO2 magnetic nanoparticles and sodium acetate solution are added to the mixed solution obtained in step (1), followed by solvent thermal reaction, and finally magnetic separation, washing and methanol Soxhlet extraction are sequentially performed to obtain a magnetic covalent organic polymer adsorbent, denoted as M-TpPa; the ratio of the amount of trialdehyde phloroglucinol, the mass of Fe3O4@SiO2 magnetic nanoparticles and the volume of the sodium acetate solution is 6mmol:295mg:2mL; the concentration of the sodium acetate solution is 5mol L -1 , the solvent in the sodium acetate solution is water; the temperature of the solvothermal reaction is 120° C., the time of the solvothermal reaction is 72 hours, and the solvothermal reaction is carried out in an autoclave; the magnetic separation is carried out by using a magnet, and the washing is first washed with methanol and then washed with water;
[0112] The preparation method of trialdehyde phloroglucinol in step (1) and the preparation method of Fe3O4@SiO2 magnetic nanoparticles in step (2) are the same as those in Example 1.
[0113] Comparative Example 2
[0114] A method for preparing a magnetic sulfonated covalent organic polymer adsorbent:
[0115] (1) firstly, trialdehyde phloroglucinol and 2,5-diaminobenzenesulfonic acid (Pa-SO3H) are mixed, then a solvent is added, and finally an ultrasonic treatment is performed for 10 minutes to obtain a mixed solution; the molar ratio of the trialdehyde phloroglucinol and 2,5-diaminobenzenesulfonic acid is 6:9; the solvent is a mixture of 1,4-dioxane and mesitylene, and the volume ratio of 1,4-dioxane and mesitylene is 1:4; the molar ratio of the trialdehyde phloroglucinol to the volume of the solvent is 0.6 mmol:10 mL;
[0116] (2) Adding Fe3O4@SiO2 magnetic nanoparticles and acetic acid solution to the mixed solution obtained in step (1), then performing a solvothermal reaction, and finally performing magnetic separation, washing and methanol Soxhlet extraction in sequence to obtain a magnetic sulfonated covalent organic polymer adsorbent, denoted as M-TpPa-SO3H; the ratio of the amount of trialdehyde phloroglucinol, the mass of Fe3O4@SiO2 magnetic nanoparticles and the volume of the acetic acid solution is 6mmol:295mg:2mL; the concentration of the acetic acid solution is 5mol L -1 , the solvent in the acetic acid solution is water; the temperature of the solvothermal reaction is 120° C., the time of the solvothermal reaction is 72 hours, and the solvothermal reaction is carried out in an autoclave; the magnetic separation is carried out by using a magnet, and the washing is first washed with methanol and then washed with water;
[0117] The preparation method of trialdehyde phloroglucinol in step (1) and the preparation method of Fe3O4@SiO2 magnetic nanoparticles in step (2) are the same as those in Example 1.
[0118] Thermogravimetric experiments were performed on the M-TpPa-SO3Na, M-TpPa and M-TpPa-SO3H obtained in Example 1 and Comparative Examples 1 to 2. The specific operation was as follows: equal masses of M-TpPa-SO3Na, M-TpPa and M-TpPa-SO3H were heated to 700°C, and the weights of M-TpPa-SO3Na, M-TpPa and M-TpPa-SO3H at different temperatures were recorded. The weight loss curves obtained were as follows: Figure 7 As shown. Figure 7 It can be seen that M-TpPa-SO3Na begins to lose weight significantly at about 220°C, indicating that the M-TpPa-SO3Na provided by the present invention has good thermal stability. At the same time, the weight loss curve of M-TpPa-SO3H is similar to that of M-TpPa-SO3Na, while the weight loss curve of M-TpPa is better, indicating that the introduction of sulfonic acid groups will slightly reduce the thermal stability of the material.
[0119] The M-TpPa-SO3Na obtained in Example 1 and the M-TpPa-SO3H obtained in Comparative Example 2 were observed using an X-ray diffractometer. The obtained X-ray diffraction patterns are as follows: Figure 8 As shown. Figure 8 It can be seen from the characteristic peaks of 7.3° and 10.9° that M-TpPa-SO3Na and M-TpPa-SO3H have high crystallinity.
[0120] Application Example 1
[0121] In order to test the test accuracy of the detection method provided by the present invention, a solution with a known concentration of the substance to be detected is used as the sample solution to be tested; the preparation method of the sample solution to be tested is: dissolving DFZ, TFM, HFM, TFZ, FFX and CFZ in methanol to obtain the sample solution to be tested;
[0122] In the sample solution to be tested, the concentrations of DFZ, TFM, HFM, TFZ, FFX and CFZ were 50 ng·g -1 , the salinity of the sample solution to be tested is 0, and the pH value of the sample solution to be tested is 7;
[0123] A method for detecting phenylurea:
[0124] (1) Take three portions of sample solution with a volume of 50 mL each and the same composition, and measure 50 mL of the sample solution into a 150 mL conical flask respectively, then evenly disperse 25 mg of the M-TpPa-SO3Na obtained in Example 1 in the sample solution for extraction and adsorption, and finally separate the M-TpPa-SO3Na from the sample solution with an external magnet to obtain a saturated adsorbent; the extraction and adsorption are carried out under oscillation conditions, and the extraction and adsorption time is 5 min;
[0125] (2) The adsorbed magnetic adsorbent obtained in step (1) is transferred to a 10 mL glass centrifuge tube, and then the residual sample solution is removed from the glass centrifuge tube with a microsyringe, and then 0.3 mL of acetonitrile is injected into the glass centrifuge tube, and vortex elution is performed for 1 min to elute BUs from the adsorbed magnetic adsorbent, and then filtered using a 0.22 μm nylon 66 organic membrane to obtain an eluent and an eluted adsorbent, and the eluted adsorbent is washed with 2 mL of acetonitrile and 2 mL of distilled water in turn to wash away the analyte remaining in the eluted adsorbent, and the obtained adsorbent can be directly reused;
[0126] (3) Take 20 μL of the eluate obtained in step (2), inject it into the HPLC system to perform high-performance liquid chromatography-ultraviolet detection on the phenylurea therein, and obtain the content of the six BUs in the 20 μL eluate, then determine the total content of the six BUs in the eluate according to the total amount of acetonitrile, and finally compare it with the standard content of the six BUs in the sample solution to obtain the adsorption amount of the adsorbent on the six BUs; the equipment and parameters of the high-performance liquid chromatography-ultraviolet detection are: chromatography system: chromatography system: 1260-HPLC (Agilent, USA), UV detector and binary pump system; chromatographic column: C18 chromatographic column (250 mm×4.6 mm, 5.0 μm); mobile phase: acetonitrile and water; the volume ratio of acetonitrile to water is 73:27, and the flow rate is 1.0 mL min -1 ; Detection wavelength: 254nm, injection volume: 20μL.
[0127] Application Example 2
[0128] The amount of M-TpPa-SO3Na in step (1) of Application Example 1 was adjusted to 30 mg, and the other conditions were the same as those of Application Example 1.
[0129] Comparative Application Examples 1 to 3
[0130] The amount of M-TpPa-SO3Na in step (1) of Application Example 1 was adjusted to 10 mg, 15 mg and 20 mg respectively, and the other conditions were the same as those of Application Example 1, and Comparative Application Examples 1 to 3 were obtained respectively.
[0131] The test results of Application Examples 1 to 2 and Comparative Application Examples 1 to 3 were compared with the actual contents, and the adsorption recovery rates under each adsorption condition were calculated as follows: Fig. 9 As shown. Fig. 9 It can be seen that as the dosage of M-TpPa-SO3Na increased from 10 mg to 25 mg, the extraction recovery of the six BUs in the sample solution gradually increased, reaching the maximum value when it increased to 25 mg, and then remained unchanged when it further increased to 30 mg, indicating that the adsorption was maximized at this time. Therefore, the dosage of M-TpPa-SO3Na was selected as 25 mg as the optimal dosage.
[0132] Application Examples 3 to 5
[0133] The oscillation time on the oscillator in step (1) of Application Example 1 was adjusted to 10 min, 15 min and 20 min respectively. The other conditions were the same as those of Application Example 1, corresponding to Application Examples 3 to 5 respectively.
[0134] Comparative Application Example 4
[0135] The oscillation time on the oscillator in step (1) of Application Example 1 was adjusted to 2 minutes, and the other conditions were the same as those of Application Example 1.
[0136] The results obtained from the tests of Application Examples 1, 3 to 5 and Comparative Application Example 4 were compared with the actual content, and the adsorption recovery rates under each adsorption condition were calculated as follows: Fig.10 As shown. Fig.10 It can be seen that as the extraction adsorption time (i.e., the oscillation time on the oscillator) increases from 2 min to 5 min, the extraction recovery rate of M-TpPa-SO3Na for BUs gradually increases, and when the extraction adsorption time increases from 5 min to 20 min, the extraction recovery rate remains basically unchanged, indicating that when the extraction adsorption time is ≥ 5 min, M-TpPa-SO3Na can completely adsorb BUs in the sample solution to be tested. Therefore, 5 min was selected as the optimal adsorption time of M-TpPa-SO3Na for BUs.
[0137] Application Examples 6 to 8
[0138] Sodium chloride was added to the sample solution of step (1) of Application Example 1 in sequence, so that the mass concentration of sodium chloride in the sample solution was 3%, 6% and 9% in sequence. Other conditions were the same as those of Application Example 1, and Application Examples 6 to 8 were obtained in sequence.
[0139] Comparative Application Examples 5-6
[0140] Sodium chloride was added to the sample solution of step (1) of Application Example 1 in sequence, so that the mass concentration of sodium chloride in the sample solution was 12% and 15% in sequence. Other conditions were the same as those of Application Example 1, and comparative application examples 5 to 6 were obtained in sequence.
[0141] The adsorption recovery rates of BUs in Application Examples 1, Application Examples 6 to 8 and Comparative Application Examples 5 to 6 are as follows: Fig.11 As shown. Fig.11 It can be seen that when the concentration of NaCl in the sample solution increases from 0 to 9%, the extraction recovery rate of M-TpPa-SO3Na for BUs does not change significantly, while when the concentration of NaCl increases from 9% to 15%, the extraction recovery rate of M-TpPa-SO3Na for BUs decreases slightly. After analysis, in the MSPE process, the ion concentration in the sample solution has two opposite effects on the extraction: on the one hand, the increase in ion concentration will reduce the solubility of the target analyte in water, thereby improving the extraction efficiency; but on the other hand, too high ion concentration will increase the viscosity of the solution, resulting in a slower dispersion of the analyte, thereby reducing the extraction efficiency, which may be due to the high ion concentration reducing the dispersion rate of the analyte. Therefore, a salt concentration of 0 was selected as the optimal adsorption salt concentration of M-TpPa-SO3Na for BUs.
[0142] Application Examples 9-11
[0143] Add 1 mol L -1 The pH of the sample solution to be tested was adjusted by adding hydrochloric acid to 1, 3 and 5 respectively. In Example 1, no hydrochloric acid and NaOH aqueous solution were added, and the pH value was 7. The other conditions were the same as those in Application Example 1, and Application Examples 9 to 11 were obtained in sequence.
[0144] Comparative Application Examples 7-8
[0145] Add 1 mol L -1 The pH of the sample solution to be tested was adjusted to 9 and 11 respectively by adding NaOH aqueous solution. Other conditions were the same as those in Application Example 1, and comparative application examples 7 to 8 were obtained in turn.
[0146] The adsorption recovery rates of BUs in Application Examples 1, Application Examples 9-11 and Comparative Application Examples 7-8 are as follows: Fig.12 As shown. Fig.12It can be seen that when the pH of the sample solution is from 1 to 3, the extraction recovery rate of M-TpPa-SO3Na for BUs increases slowly, when the pH of the sample solution is from 3 to 7, the extraction recovery rate remains stable, when the pH of the sample solution is from 7 to 9, the extraction recovery rate decreases slowly, and when the pH of the sample solution is from 9 to 11, the extraction recovery rate decreases rapidly. After analysis, the pH of the sample solution may have a significant effect on the extraction recovery rate of certain analytes, because it will affect the existence form of the analytes and may also affect the stability of the adsorbent. BUs are weakly acidic compounds, and the pKa values of DFZ, TFM, HFM, TFZ, FFX and CFZ are 8.78, 9.33, 8.54, 8.16, 8.66 and 8.10, respectively. Under conditions where the pH is greater than 7, the reduction in the extraction recovery rate of BUs may be due to the hydrolysis of BUs under alkaline conditions. On the other hand, the low extraction recovery rate in acidic and alkaline media may be due to the partial decomposition of the M-TpPa-SO3Na composite material.
[0147] The acid-base stability of M-TpPa-SO3Na provided in Example 1 was tested by: M-TpPa-SO3Na was respectively -1 Hydrochloric acid and 3 mol L -1 Soak in NaOH aqueous solution for 6 hours, and then perform FT-IR analysis on the soaked M-TpPa-SO3Na. The results are as follows Fig.13 As shown. Fig.13 It can be seen that after immersion in acidic or alkaline conditions, the Fe-O-Fe -1 The peak intensity at 27° was greatly reduced, indicating that its magnetism was lost, which may be the reason why the extraction recovery rate decreased when the pH of the solution sample was between 1 and 3 and 7 and 9.
[0148] Taking into account the effects of the above-mentioned acid and alkali on the stability of M-TpPa-SO3Na and the extraction recovery rate of BUs, and considering that the pH values of the environmental water, pear juice and honey samples currently studied are all around 7, the pH value of 7 was finally selected as the optimal adsorption pH value of M-TpPa-SO3Na for BUs, without the need to adjust the pH value of the sample solution during the actual detection process.
[0149] Application Examples 12-13
[0150] The acetonitrile in step (2) of Application Example 1 was replaced by methanol and acetone respectively, and the other conditions were the same as those of Application Example 1, to obtain Application Examples 12 to 13 in sequence.
[0151] The adsorption recovery rates of BUs in Application Examples 1 and 12-13 are as follows: Fig.14 As shown, Fig.14In the figure, the horizontal axis from left to right is methanol, acetonitrile and acetone. Fig.14 It can be seen that when different organic solvents are selected as eluents, the recoveries of six different BUs are different, indicating that different organic solvents have different efficiencies for eluting BUs from M-TpPa-SO3Na. Among them, acetonitrile, a mobile phase component, is selected as the eluent, and its elution efficiency is higher than that of acetone and methanol. In order to effectively elute the target analytes from M-TpPa-SO3Na, acetonitrile is preferably selected as the eluent.
[0152] Application Examples 14-17
[0153] The amount of acetonitrile in step (2) of Application Example 1 was adjusted to 0.6 mL, 0.9 mL, 1.2 mL and 1.5 mL respectively, and the other conditions were the same as those of Application Example 1, and Application Examples 22 to 25 were obtained in sequence.
[0154] The adsorption recovery rates of BUs in Application Examples 1 and 14 to 17 are as follows: Fig.15 As shown. Fig.15 It can be seen that as the volume of the eluent increased from 0.3 mL to 0.9 mL, the extraction recovery rate of BUs gradually increased. When the volume of acetonitrile increased from 0.9 mL to 1.5 mL, the extraction recovery rate remained basically unchanged, indicating that 0.9 mL of acetonitrile can completely elute BUs from M-TpPa-SO3Na.
[0155] The effect of the volume of the eluent on the sensitivity of M-TpPa-SO3Na in Application Examples 1 and Application Examples 14 to 17 is as follows: Fig.16 As shown. Fig.16 It can be seen that as the eluent volume increases from 0.3 mL to 1.5 mL, the detection sensitivity (expressed in peak area) of the analyte decreases due to the dilution effect, which will affect the reuse of M-TpPa-SO3Na.
[0156] By combining Fig.15 and Fig.16 ,In order to improve the sensitivity of M-TpPa-SO3Na, although BUs cannot be completely eluted, 0.3mL acetonitrile is still selected as the optimal volume of the eluent, because in actual operation, the recovery rate reflects the adsorption effect of the material, and then the instrumental method is used for trace analysis to reduce errors. The eluted M-TpPa-SO3Na needs to be washed with 1mL acetonitrile and 1mL distilled water before the next reuse.
[0157] Comparative Application Example 9
[0158] The M-TpPa-SO3Na in step (1) of Application Example 1 was replaced with the M-TpPa prepared in Comparative Example 1.
[0159] Comparative Application Example 10
[0160] The M-TpPa-SO3Na in step (1) of Application Example 1 was replaced with the M-TpPa-SO3H prepared in Comparative Example 2.
[0161] In comparative application example 9, after using M-TpPa to adsorb BUs in the sample solution to be tested, the adsorption recovery rate obtained was only 35.1% to 40.8%; in comparative application example 10, after using M-TpPa-SO3H to adsorb BUs in the sample solution to be tested, the adsorption recovery rate obtained was only 78.6% to 79.4%. By comparing with application example 1, it can be seen that the M-TpPa-SO3Na prepared by the present invention has a higher adsorption recovery rate for BUs, and can effectively determine the content of BUs in environmental water, pear juice, honey, various meat and vegetable samples.
[0162] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A magnetic sulfonated covalent organic polymer adsorbent, comprising a covalent organic framework and Fe3O4@SiO2 magnetic nanoparticles loaded on the covalent organic framework; the building units of the covalent organic framework are trialdehyde phloroglucinol and sodium 2,5-diaminobenzenesulfonate.
2. The magnetic sulfonated covalent organic polymer adsorbent according to claim 1, characterized in that: The molar ratio of trialdehyde phloroglucinol to sodium 2,5-diaminobenzenesulfonate in the covalent organic framework is 6:(8-10).
3. The magnetic sulfonated covalent organic polymer adsorbent according to claim 1 or 2, characterized in that: The ratio of the amount of trialdehyde phloroglucinol in the covalent organic framework to the mass of Fe3O4@SiO2 magnetic nanoparticles is 6mmol:(280-300)mg.
4. The preparation method according to claim 3, characterized in that: The Fe3O4@SiO2 magnetic nanoparticles include Fe3O4 nanoparticles and SiO2 coated on the surface of the Fe3O4 nanoparticles.
5. The method for preparing the magnetic sulfonated covalent organic polymer adsorbent according to any one of claims 1 to 4, comprising the following steps: (1) mixing trialdehyde phloroglucinol, 2,5-diaminobenzenesulfonic acid and an organic solvent to obtain a mixed solution; (2) The mixed solution obtained in step (1) is mixed with Fe3O4@SiO2 magnetic nanoparticles and sodium acetate solution and then subjected to a solvothermal reaction to obtain a magnetic sulfonated covalent organic polymer adsorbent.
6. The preparation method according to claim 5, characterized in that: In the step (1), the ratio of the amount of trialdehyde phloroglucinol to the volume of the organic solvent is 0.6 mmol: (8-15) mL.
7. The preparation method according to claim 5, characterized in that: The molar ratio of trialdehyde phloroglucinol in the mixed solution of step (2) to sodium acetate in the sodium acetate solution is 6:(0.05-0.2).
8. The preparation method according to claim 5, characterized in that: The temperature of the solvent thermal reaction in step (2) is 100 to 150° C., and the time of the solvent thermal reaction is 48 to 108 hours.
9. Use of the magnetic sulfonated covalent organic polymer adsorbent according to any one of claims 1 to 4 or the magnetic sulfonated covalent organic polymer adsorbent prepared by the preparation method according to any one of claims 5 to 8 in adsorbing phenylurea.
10. A method for detecting phenylurea, characterized in that: The following steps are involved: 1) Mixing a sample solution to be tested and an adsorbent for extraction and adsorption, and then performing magnetic separation to obtain a saturated adsorbent; the adsorbent is the magnetic sulfonated covalent organic polymer adsorbent according to any one of claims 1 to 4 or the magnetic sulfonated covalent organic polymer adsorbent prepared by the preparation method according to any one of claims 5 to 8; the salinity of the sample solution to be tested is ≤9%, and the pH value of the sample solution to be tested is 3 to 7; The volume ratio of the sample solution to be tested to the mass ratio of the magnetic sulfonated covalent organic polymer adsorbent is 50 mL: (25-30) mg; the extraction and adsorption time is 5-20 min; 2) eluting the saturated adsorbent obtained in step 1) and filtering to obtain an eluent and an eluted adsorbent; the eluent used for the elution is methanol, acetone or acetonitrile; the ratio of the mass of the magnetic sulfonated covalent organic polymer adsorbent to the volume of the eluent is 25 mg: (0.3-0.9) mL; 3) performing high performance liquid chromatography-ultraviolet detection on the phenylurea in the eluent obtained in step 2) to obtain the adsorption amount of the adsorbent on the phenylurea.